Implementasi Pembelajaran Berdiferensiasi untuk Meningkatkan Hasil Belajar Peserta Didik - Anjelina, Windri; Hambali, Hambali (Jurnal Pendidikan Teknik Elektro, 2024)
This research was conducted to determine the implementation of differentiation learning using the Problem-based Learning ( PBL ) model at SMK Negeri 1 Sutera. By realizing that each student has a different background, learning profile, interest, and learning speed, this research aims to map students learning needs based on interest, learning readiness, and learning profile (learning style). Learning is then designed by providing various strategies, materials, and learning methods according to the mapping result. Results of observation in educational classes. Based on data analysis from experimental class learning outcomes, this research shows that average student learning outcomes have increased. According to the sketch results, learning is then designed by providing various choices of strategies, materials, and learning methods. Observation results in education classes. In this research, based on data analysis of experimental class learning outcomes, it can be seen that the average student learning outcomes have increased and obtained N-Gain with medium criteria. This shows that this strategy is quite effective in accommodating the different learning needs of students in one class.